Knowledge, attitudes, and uptake of mental health services by secondary school students in Gweru, Zimbabwe - Khombo, Sibusiso; Khombo, Kennedy; Stoddart, Robert Shalom; Sifelani, Innocent; Sibanda, Theresi (Frontiers in Psychology, 2023)
The study sought to investigate and analyze knowledge and attitudes regarding up taking of mental services by secondary school students in Gweru. It sought to establish how much the students knew on mental health services and what their perceptions and willingness to utilize them were. Using a purely qualitative approach, eighteen (18) students from various secondary schools in Gweru were interviewed. Findings revealed that most secondary school students were aware of the existence of the term ‘mental health’ and related it to the psychiatric patients and schizophrenics seen wondering about in the cities. They felt that mental health services were strictly for the mentally unwell ‘mapenzi’ and thus reported no need to use the services.